Water Stress Corrosion in Bonded Structures. (18th February 2015) - Fournel, F.; Martin-Cocher, C.; Radisson, D.; Larrey, V.; Beche, E.; Morales, C.; Delean, P. A.; Rieutord, F.; Moriceau, H.
Abstract : Direct bonding is now a well-known technique to join two flat surfaces without any additional material. This technique is used in many applications and especially in SOI (Silicon-On-Insulator) elaboration or in some backside imager manufacturing processes which are now almost in mass production. Direct bonding mechanism study is then very important in order to clearly understand this bonding behavior. Especially in the case of silicon or silicon dioxide hydrophilic surface, the role of water is essential. Water could lead to lots of different reactions at the bonding interface and especially the water stress corrosion could play an important role in the direct bonding mechanism.